The Public Health Leadership and Implementation Academy (PH-LEADER) for Non-Communicable Diseases. Issue 3 (2nd July 2016) - Galaviz, Karla I.; Narayan, K. M. Venkat; Manders, Olivia; McFarland, Deborah A.; Goenka, Shifalika; Torres-Mejía, Gabriela; Reddy, K. Srinath; Lozano, P. Rafael; Magaña-Valladares, Laura; Prabhakaran, Dorairaj; Ali, Mohammed K.
Abstract: Low- and middle-income countries (LMICs) are experiencing a growing burden of non-communicable diseases (NCDs) and confront challenges of leadership, lack of local data and evidence, and gaps in implementation of successful interventions. To address these challenges, we designed an interdisciplinary training program, the Public Health Leadership and Implementation Academy (PH-LEADER) for NCDs. The year-long program has three components; a two-month preparation period; a three-week, in-person summer short course; and an in-country mentored project phase. The training was directed at mid-career, high-potential public health professionals from LMICs who are involved in NCDs prevention and control. We collected demographic data and information about achievements and products attained from participation in the program among trainees. Over four and a half years (2012–2016), 67 NCDs professionals (mean age 38.7 years; 58% male) from 11 countries have been trained. The training program has promoted the design and implementation of 49 projects focused on implementation of programs and policies addressing NCDs; 20 manuscripts submitted for publication; and four abstracts submitted for conference presentations. The PH-LEADER program promotes the design and implementation of evidence-based strategies to address NCDs in LMICs. Impact on trainee implementation research capacity and leadership skills and ultimately on NDCs prevention and control is yet to be assessed.